PENERAPAN GAYA KEPEMIMPINAN TRANSFORMING BRANCH MANAGER KCP BANK SYARIAH - Harbani, Harbani; Amansyah, Farida; Yahya, Andi; Sari, Mawar (Journal of Business Administration (JBA), 2024)
This research was aimed to determine how the implementation Transforming Leadership Style Impelementation of Branch Manager KCP Indonesian Islamic Bank Tamalanrea 1 Makassar for the period of 2021-2024.The research method used was descriptive research. The sampling technique used was saturated sampling technique where the entire 23 population were taken as samples. Measurement of data was using a likert scale and data collection methods through observation, questionnaires dan interviews. The data analysis used was quantitative analysis supported by qualitative analysis and data processing using frequency distribution table.Based on the research which has been done, the results were the implementation of the Transforming Leadership of Branch Manager Indonesian Islamic Bank Tamalanrea 1 Makassar for the Period 2021-2024 shows a total 120 (34.09%) where this value is in the highest score range with the interpretation of "Not Good". Especially in the indicators of planning, grouping and motivating. So in this case the Transforming Leadership of Branch Manager KCP Indonesian Islamic Bank Tamalanrea 1 Makassar for the Period of 2021-2024 is categorized as not good, which means its implementation has not been good.Based on the conclusions of this research, the author suggests that the Branch Manager in planning an activity should always refer to the vision/goals of the organization so that what is done or planned is more targeted. Branch Manager is expected to be more familiar and know the qualities and capacities of their employees, so that employee work placements can be in accordance with their respective fields. Then the Branch Manager is expected to pay attention to relationships with his employees. For example, communicating with employees about their hopes and desires. That way, employees feel cared for and will build their enthusiasm to work actively.